Eric Drummond and his Legacies - Macfadyen, David. author. aut Link
XXIX, 361 p. 17 illus., 8 illus. in color.
Keywords: "This well-researched book does justice finally to a forgotten pioneer of international cooperation. It explores Drummond’s legacy—an international civil service with integrity, intelligence, independence, and impartiality—which remains more aspiration than reality. Discover why that vision remains pertinent." —Thomas G. Weiss, City University of New York, USA "Part biography, part institutional history, this is a fitting tribute to the spirit of internationalism on the eve of the League’s centenary. The ethos of an impartial yet committed international civil service permeates the book -- and it is published when that ethos is needed more than ever." —Christian J. Tams, University of Glasgow, UK This book provides a new assessment of Eric Drummond, the first Secretary-General of the League of Nations. Part 1 describes his character and leadership. His influence in shaping the International Civil Service is the subject of Part 2. Part 3 shows the large-scale absorption of League programmes, practices and staff into the UN and its Specialized Agencies. David Macfadyen is Fellow of the Royal College of Physicians of Edinburgh, UK, and has worked at a senior level in the World Health Organization (WHO). His research interests include the History of Medicine, which he has studied at the University of Glasgow, UK. Michael Davies is a former staff member of the Food and Agriculture Organization (FAO) and the Inter-American Development Bank. He is the author of International Organizations: A Companion and The Administration of International Organizations. Marilyn Carr has worked for the UN Economic Commission for Africa and the UN Development Fund for Women. She studied Development Economics at the University of Sussex, UK, and is the author of many books and articles on science, technology and women’s economic empowerment. John Burley was an economic adviser to the Government of Uganda before working for the UN, including the UN Development Programme (UNDP). He was a Director at the UN Conference for Trade and Development and has contributed to a number of published studies of the UN system.